2011
DOI: 10.1111/j.1365-2036.2010.04564.x
|View full text |Cite
|
Sign up to set email alerts
|

A 13-nation population survey of upper gastrointestinal symptoms: prevalence of symptoms and socioeconomic factors

Abstract: SUMMARY BackgroundPrevious data collected in separate studies using various different survey instruments have suggested some variability in the prevalence of symptoms between nations. However, there is a lack of studies which assess and compare the prevalence of upper gastrointestinal symptoms contemporaneously in various countries using a uniform, standardised method.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
18
0
6

Year Published

2013
2013
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(25 citation statements)
references
References 35 publications
1
18
0
6
Order By: Relevance
“…In this context, environmental factors such as specific diets, lifestyle, or hygiene factors at key stages of life may contribute to the manifestation of FGIDs. Indeed, in contrast to IBS, a recent study demonstrated that the prevalence of dyspeptic symptoms was inversely associated with the GDP per capita [7].…”
Section: Early Lifementioning
confidence: 99%
See 1 more Smart Citation
“…In this context, environmental factors such as specific diets, lifestyle, or hygiene factors at key stages of life may contribute to the manifestation of FGIDs. Indeed, in contrast to IBS, a recent study demonstrated that the prevalence of dyspeptic symptoms was inversely associated with the GDP per capita [7].…”
Section: Early Lifementioning
confidence: 99%
“…In an assessment of more than 23,000 population-based subjects, the prevalence of any uninvestigated dyspepsia was highly variable across various geographic regions, ranging from 24 to 45 % [7]. IBS affects 7-21 % of various populations [8], or around 11 % globally [9].…”
Section: Introductionmentioning
confidence: 99%
“…The prevalence of upper gastrointestinal symptoms was 44.9% in USA (1) and 38% in European countries. It was highest in Central and East European countries and was closely associated with socioeconomic factors (2).…”
Section: Introductionmentioning
confidence: 99%
“…Recently, a striking inverse relationship between symptom prevalence and gross domestic product in the respective ­European countries was observed (Fig. 1) [8]. …”
Section: Pathophysiologic Concepts In Fgidmentioning
confidence: 99%
“…The dataset included 23,164 population-based subjects [8]. The size of the bullets reflects the relative sample size (reproduction with permission).…”
Section: Pathophysiologic Concepts In Fgidmentioning
confidence: 99%